2017
DOI: 10.1016/j.snb.2017.01.091
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural control of porous In2O3 powders prepared by ultrasonic-spray pyrolysis employing self-synthesized polymethylmethacrylate microspheres as a template and their NO2-sensing properties

Abstract: NO2-sensing properties of porous In2O3 powders prepared by ultrasonic-spray pyrolysis employing self-synthesized polymethylmethacrylate (PMMA) microspheres as a template have been investigated in this study. The PMMA microspheres were synthesized by ultrasonicassisted emulsion polymerization. The pore-size distribution, crystallite size (CS), and specific surface area (SSA) of the porous In2O3 powders prepared with the PMMA microspheres with a diameter of ca. 77 nm (pr-In2O3(Tp), Tp: pyrolysis temperature, 600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…For an example, it was reported that porous α-Fe2O3 nanoparticles showed a better sensing performance than the dense α-Fe2O3 ones [21,22]. Due to this reason, much effort has been made so far to prepare and characterize porous In2O3 nanostructures for sensing applications [23][24][25][26]. For examples, Sun et al [23] prepared mesoporous In2O3 using a nanocasting method, and obtained a significantly improved response to ethanol (with a detection limit of 0.05 at 220 o C) in comparison with the data from the bulk In2O3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For an example, it was reported that porous α-Fe2O3 nanoparticles showed a better sensing performance than the dense α-Fe2O3 ones [21,22]. Due to this reason, much effort has been made so far to prepare and characterize porous In2O3 nanostructures for sensing applications [23][24][25][26]. For examples, Sun et al [23] prepared mesoporous In2O3 using a nanocasting method, and obtained a significantly improved response to ethanol (with a detection limit of 0.05 at 220 o C) in comparison with the data from the bulk In2O3.…”
Section: Introductionmentioning
confidence: 99%
“…Shanmugasundaram et al [15] reported that mesoporous In2O3 nanocubes prepared using a hydrothermal method showed a superior sensitivity to H2 at a very low concentration of 100 ppb. Recently Wang et al [24] reported that the sensor made of In2O3 nanosheets with mesopores showed a high response of 213 toward 10 ppm NOx with a low detection limit of 10 ppb at 120 o C. Zhang et al [25] prepared hierarchical Au-loaded In2O3 porous nanocubes using a hydrothermal process, and the sensor made using these porous nanocubes showed a response of 37 to 100 ppm formaldehyde at 240 o C. Hyodo et al [26] reported that sensors made of porous In2O3 powders prepared using ultrasonic-spray pyrolysis exhibited a better response to 10 ppm NO2 than the sensor made of the conventional In2O3 powders. Clearly, porous In2O3 nanostructures have exhibited excellent sensing properties, and therefore will be used in our proposed dual functional sensors for both UV light and H2S sensing.…”
Section: Introductionmentioning
confidence: 99%
“…65 • C within 15 min. After the ultrasonic irradiation for 30 min, the aqueous dispersion containing PMMA microspheres was obtained (Hyodo et al, 2017). The particle-size distribution of the synthesized PMMA microspheres in the aqueous dispersion was measured at 25 • C by dynamic light scattering (DLS; Malvern Instrument Ltd., HPPS), and the average particle size of PMMA microspheres in the aqueous dispersion was confirmed as ca.…”
Section: Synthesis Of Pmma Microspheresmentioning
confidence: 99%
“…Recently, we focused on the preparation of smallersized PMMA microspheres by an ultrasonic-assisted emulsion polymerization technique, and demonstrated an increase in the amount of sodium lauryl sulfate as a surfactant in the polymerization process of methyl methacrylate monomers decreased the size of the synthesized PMMA microspheres (Hyodo et al, 2013). In addition, the fabricated porous (pr-) In 2 O 3 sensor employing smaller-sized PMMA microspheres (ps: 26 nm) as a template in a precursor solution of ultrasonic spray pyrolysis was effective in improving the magnitude of NO 2 response to a low concentration of NO 2 (e.g., 1 ppm) at relatively low temperature (150 • C) (Hyodo et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation